Asuhan Kebidanan Pada Masa Kehamilan, Persalinan, Nifas, BBL, KB Dan Gambaran Pengetahuan Ibu Tentang Persalinan Pada Ny. S G1p0a0 - Miftahul Jannah (Jurnal Rumpun Ilmu Kesehatan, 2021)
Pregnancy is a physiological and natural condition that occurs in women. There are various complaints experienced by pregnant women during their pregnancy, one of the most common complaints is dizziness. Objective: LTA provides comprehensive midwifery care to pregnant, maternity, postpartum, BBL, neonate and family planning women using a midwifery management approach for Mrs "P" who complained of dizziness. Method: Care in this LTA is through interviews, observation and care management. The subject in this care is Mrs "S" at the Pratama Riyyan Kabanjahe Clinic. Results: results of comprehensive midwifery care for Mrs "S" during pregnancy in the second trimester and third trimester with dizziness, in normal labor, spontaneously without complications, in the postpartum period with normal puerperium, in BBL with BBLN, in patients. The care that mothers receive for family planning counseling is to inform the mother about normal vital signs and her current condition, provide health education about family planning effectiveness, side effects, and how to use it and explain to the mother how to space her pregnancies or to space her pregnancies. After midwifery care was provided to Mrs. S, the results of the evaluation showed that the mother was healthier and able to carry out daily activities. Based on the results of the questionnaire from assessing maternal knowledge about childbirth, it was found to be ADEQUATE with 70% results from 20 questions.